Exploration and Meaning Making in the Learning of Science - Zubrowski, Bernard (Innovations in Science Education and Technology, 2009)
This original and unorthodox book summarizes the author's present thinking about curriculum design and direct work with students. The author draws upon his varied experiences to present a case for the importance of direct engagement with phenomena and materials. He argues that this practice is more than a matter of motivating students to become engaged in inquiry. The first four chapters lay out different levels of a pedagogical approach and an overall theoretical orientation. The middle chapters focus on what might be called sensory knowledge. These are concerned with the role of different sensory engagement, movement as related to gestural representation and the role of empathy in exploration. The last four chapters are about the role of aesthetic, play, variable exploration and metaphor in their shaping of science education experiences. Each chapter is introduced with a scenario or case study describing the behavior and talk of elementary or middle school students. The intention of these scenarios is to help the reader stay grounded while considering the more abstract development of research reports and broader philosophical issues.